Natural fashion tribal decoration from Africa - Silvester, Hans 1938- (Thames & Hudson, 2009)
Over the course of numerous voyages to Africa's Omo Valley, Hans Silvester became fascinated by the beauty of the Surma, Mursi, Hamer and Kurma tribes, who share a taste for body painting and extravagant decorations borrowed from nature. This collection of photographs captures these accoutrements.